Multicultural study of entrepreneurial competencies and SMEs success in Malaysian service industry: a conceptual model - Khan, Ghazala; Ali, Mass Hareeza; Jantan, Amer Hamzah; Abdul Latiff, Ahmed Razman (Institution of Business Intelligence Innovation, 2018)
Entrepreneurial competencies (E.C) play an important part in the existence and development of Enterprises. The vital role of E.C attract researchers, to comprehend the development of the fundamental capabilities of entrepreneurs. E.C diverges across regions due to cultures. This research Paper aspires to inspect the influence of ethnicity on E.C among Malaysian SMEs owners. This research paper presents a new theoretical framework to enhance the understanding and admit the role of ethnic behavior in the growth of E.C. The hypothesized framework will also, reflects the curbing position of environmental turbulence, government support and its connection of E.C with SMEs’ business success. Besides this, a new conceptual model is envisioning the theoretical framework to inspect the impact of under considered variables on SMEs success. Consequently, the classified competencies will be helpful in SMEs successful growth. The progression of SMEs in Malaysia Will contribute in achievement of Transformational National 2050 (TN50) initiative in the accomplishment of a highincome nation status